The association of self-rated health with physical activity and demographic factors : a study in primary care from Northwest of Iran - Moradi, Hanieh; Raeisvandi, Abouzar; Bahrami, Mahdie; Amerzadeh, Mohammad; Abbasi, Mozhgan; Hosseinkhani, Zahra; Osooli, Mehdi ; 0000-0002-9862-3665 (BMC Primary Care, 2025)
Background: Self-rated health (SRH) is an international measure and indicator of mortality and morbidity that can be used as a mortality predictor in adulthood. This study aimed to examine the status of SRH among adults in Qazvin Province and its relationship with physical activity levels and demographic factors in primary care centers. Methods: This is a cross-sectional study. We included data from 1223 individuals 18–64 years residing in Qazvin Province, located in northwest Iran. Participants were selected using the electronic health records in primary care and through a multi-stage cluster sampling method. Demographic and self-reported health information were collected using a self-administered questionnaire. SRH has been categorized ranging from very good to very poor. We estimated the Odds Ratio (OR) of suboptimal SRH in association with level of physical activity and adjusting for age, sex, marital status, and employment. Results: In this study, 407 (33.2%) of the participants, including 37% of female and 26% of male, exhibited sub-optimal SRH, while overall 34% reported no physical activity per week. The percentage of individuals with sub-optimal SRH was higher among those with no physical activity, older age groups, female sex and retirees. SRH was associated with having no physical activity (OR: 1.55; 95% CI: 1.13, 2.14), older age, female sex (OR: 1.75; 95% CI: 1.23, 2.48), and being retired (OR: 1.94; 95% CI: 1.05, 3.96). Conclusions: About one-third of the individuals demonstrated suboptimal SRH. Health policymakers must promote physical activity programs, especially among older age groups, retirees, and females to improve SRH in the community.
Publisher Copyright: © The Author(s) 2025.
Keywords: Iran; Physical activity; Primary care; Self-rated health